Multi‐phase multi‐layer mechanistic dermal absorption (MPML MechDermA) model to predict local and systemic exposure of drug products applied on skin - Nikunjkumar Patel; James F. Clarke; Farzaneh Salem; Tariq Abdulla; Frederico Martins; Sumit Arora; Eleftheria Tsakalozou; Arran Hodgkinson; Omid Arjmandi‐Tash; Sinziana Cristea; Priyanka Ghosh; Khondoker Alam; et al. (CPT: Pharmacometrics & Systems Pharmacology, 2022)
Abstract Physiologically‐based pharmacokinetic models combine knowledge about physiology, drug product properties, such as physicochemical parameters, absorption, distribution, metabolism, excretion characteristics, formulation attributes, and trial design or dosing regimen to mechanistically simulate drug pharmacokinetics (PK). The current work describes the development of a multiphase, multilayer mechanistic dermal absorption (MPML MechDermA) model within the Simcyp Simulator capable of simulating uptake and permeation of drugs through human skin following application of drug products to the skin. The model was designed to account for formulation characteristics as well as body site‐ and sex‐ population variability to predict local and systemic bioavailability. The present report outlines the structure and assumptions of the MPML MechDermA model and includes results from simulations comparing absorption at multiple body sites for two compounds, caffeine and benzoic acid, formulated as solutions. Finally, a model of the Feldene (piroxicam) topical gel, 0.5% was developed and assessed for its ability to predict both plasma and local skin concentrations when compared to in vivo PK data.